2021
DOI: 10.3389/fimmu.2021.640595
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell-Derived Extracellular Vesicles Restore Thymic Architecture and T Cell Function Disrupted by Neonatal Hyperoxia

Abstract: Treating premature infants with high oxygen is a routine intervention in the context of neonatal intensive care. Unfortunately, the increase in survival rates is associated with various detrimental sequalae of hyperoxia exposure, most notably bronchopulmonary dysplasia (BPD), a disease of disrupted lung development. The effects of high oxygen exposure on other developing organs of the infant, as well as the possible impact such disrupted development may have on later life remain poorly understood. Using a neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Mesenchymal fibroblast cells were demonstrated to be required for formation of thymic microenvironment by producing retinoic acid ( 92 ). Mesenchymal stromal cells or their extracellular vesicles showed great potential in promoting thymic epithelial cell expansion and differentiation ( 93 , 94 ). To further investigate the factors mediating the development of TECs by mesenchymal fibroblast, we systematically investigated the ligand–receptor interactions specifically expressed across these cell types (see Materials and Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Mesenchymal fibroblast cells were demonstrated to be required for formation of thymic microenvironment by producing retinoic acid ( 92 ). Mesenchymal stromal cells or their extracellular vesicles showed great potential in promoting thymic epithelial cell expansion and differentiation ( 93 , 94 ). To further investigate the factors mediating the development of TECs by mesenchymal fibroblast, we systematically investigated the ligand–receptor interactions specifically expressed across these cell types (see Materials and Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…All EV samples prepared and analyzed as previously published [ 20 , 32 , 34 ]. All EV samples were diluted in PBS to a final volume of 1 mL.…”
Section: Methodsmentioning
confidence: 99%
“…To date, our understanding of stromal cells, such as adipocytes, fibrocytes, fibroblasts, and mesenchymal stem cells (MSCs), along with their secreted EVs, has been reported in studies that mediate disease-exacerbating changes in asthma [ 17 ], cancer [ 18 , 19 , 20 , 21 , 22 ], fibrosis [ 23 , 24 , 25 ], and cardiovascular diseases [ 26 , 27 , 28 ], but also show the therapeutic action of MSC-EVs by targeting different tissues, including the lungs, placenta, and thymus [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. By focusing on the cornea, studies have investigated how corneal MSC-EVs can improve corneal epithelial wound healing, reduce corneal epithelial defects, and promote scarless stromal recovery post-corneal injury in vivo [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies revealed that MSC-EVs promoted an immunosuppressive in bone marrow-derived myeloid cells phenotype. A study ( 55 ) demonstrated that MSC-EVs treatment represents a promising restorative therapeutic approach for oxygen-induced thymic injury, thus promoting normal development of both central tolerance and adaptive immunity.…”
Section: The Mechanism Of Mesenchymal Stromal Cells Derived Extracell...mentioning
confidence: 99%